Serum cytokine/chemokine levels in a patient with perifolliculitis capitis abscedens et suffodiens (dissecting cellulitis) successfully treated with the tumour necrosis factor α inhibitor adalimumab - Yuta Koike; Naoko Hattori; Hiroyuki Murota (Wiley, 2022)
Abstract Perifolliculitis capitis abscedens et suffodiens (PCAS), also called dissecting cellulitis, is a refractory disease characterized by deep follicular occlusion, ruptures and infections. Here, we present a case of PCAS in a young man whose scalp showed subcutaneous nodules with purulent secretions, and geographic hair loss from the occipital region. Since the PCAS was refractory to treatment by incision, drainage and systemic antibiotics, we administered adalimumab, an antitumour necrosis factor (TNF) antibody. After 4 months of treatment with adalimumab, the PCAS improved markedly, with flattening of the scalp lesions and hair regrowth. We examined the serum levels of cytokines/chemokines using a Magnetic Bead Panel Plate Assay to compare levels before and at 3 months post‐adalimumab treatment. The results showed a slight decrease in TNF‐α levels and a significant reduction in the expression of cytokines or chemokines that promote macrophage and neutrophil migration, suggesting that these factors might contribute to the pathogenesis of PCAS.